Assessment of Health Problems and Social Needs of Elderly in old age Homes of Biratnagar Metropolitan - Bhandari, Menuka; Niroula, Alweena; Chaudhary, Shamila (Dristikon: A Multidisciplinary Journal, 2020)
Nepal is also witnessing the expansion of life span and hence an enhancement in the population of the elderly. In Nepal, individuals over 60 years of age are considered elderly. According to the 2011 census of Nepal, there were 2.1 million elderly inhabitants, which constitute 8.1percent of the total population in the country. Pashupati Bridrashram the only one shelter for elderly people run by the government which was established in 1976 as the first residential facility for elders. This study was conducted to assess the health and social needs of elderlyresiding at Birateshwor Briddhashram and Mahila Jagriti Briddhashram Biratnagar. Descriptive cross sectional research design has been used to describe characteristics of apopulation. There are four registered old age home in Biratnagar Metropolitan City, amongthem only two were selected purposively. Non random sampling technique has been used in which Purposive Sampling method has been adopted. Both health and social needs we reassessed using semi-structured interview schedule which consisted of multiple response questionnaire. There were fifty-seven elders, only forty were selected purposively who can give their information, twenty-four females and sixteen males were selected for interview. Most of the elders came to old age home because of lack of own shelter, sixty percent elders have no any children; mostly they were widow or widower. Majority of them had vision (60 %), walking (46%), hearing problems (33 %) and minority (10 %) have inability problems in moving extremities, difficulty in talking. Only a few elders came there because of maltreatment by their family members. The study has suggested for establishment of health post or healthcare center, provision of ambulance to meet their health needs and importance of care taker to make their life easier, provision of television, kitchen garden, temple to meet their social and spiritual needs.